أثر الوسائط السمعية البصرية عبر كانڤا على تعلم العربية لدى طلبة الصف الثامن - Ahmad Nur Mizan; Zulhannan; Elin Novalia; Tamer Sa’ad Ibrahim Khedr (Arabiyyatī: Journal of Arabic Language Education, 2025)
This study aims to examine the significant effect of the use of audiovisual media based on the Canva application on the learning outcomes of Arabic language class VIII students at MTs Al-Muhajirin Panjang. The background of this study is the importance of using interesting learning media to increase student motivation and understanding. The method used is quantitative with a Quasi-Experimental design, namely pretest-posttest control group design. The research population involved two classes, class 8.1 as the experimental group and 8.2 as the control group, with data collection using validated tests and analysed using SPSS 25. The results showed that the mean score of students in the experimental group (81.40) was higher than the control group (77.20), and the t-test results showed a significance value of 0.000 < 0.05, which means the null hypothesis is rejected and the alternative hypothesis is accepted. The conclusion of this study is that the use of audiovisual media based on the Canva application has a positive effect on students' Arabic learning outcomes.